Observed decline in Titan's thermospheric methane due to solar cycle drivers. Issue 10 (14th October 2014) - Westlake, J. H.; Waite, J. H.; Bell, J. M.; Perryman, R.
Abstract We present Cassini Ion and Neutral Mass Spectrometer observations of Titan's N2 and CH4 from Cassini flybys of Titan spanning the time period from 2004 to 2013 representing 9 years of in situ neutral density observations. This data reveal an upward trend in CH4 mixing ratios during the extended solar minimum encountered prior to 2011 followed by a downward trend in the mixing ratios of CH4 after the onset of solar maximum conditions in 2011. Through modeling studies using the time‐dependent Titan Global Ionosphere‐Thermosphere Model we show that this trend is due to enhanced photodestruction of CH4 in Titan's thermosphere from the increased solar EUV/UV flux during solar maximum times. The enhanced photodestruction of the methane leads to an increase in production of large hydrocarbons as observed in the enhanced production of large hydrocarbon ions and a twofold increase in the downward flux of C2 and larger hydrocarbons during solar maximum. Methane in the thermosphere is resupplied through upward flux from the lower thermosphere and stratosphere resulting in a refilling of the thermospheric methane on timescales of three Earth years. From this calculation it is expected that Titan's thermospheric methane will recover in the 2015 timeframe.